2010
DOI: 10.1111/j.1469-0691.2009.02774.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the presence of high-risk human papillomaviruses and Id gene expression in Syrian women with cervical cancer

Abstract: Infection by high-risk human papillomaviruses (HPVs) is considered to be the central cause of invasive cervical cancer. Previously reported studies have shown that Id genes regulate cell invasion and metastasis in several human carcinomas including cervical cancer. In order to investigate the correlation between high-risk HPVs and Id genes in human cervical cancer, the presence of high-risk HPVs and their association with Id gene expression was examined using PCR methods and tissue microarray analyses in a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 21 publications
4
34
3
Order By: Relevance
“…Similar detection rates of these two HPV types have been reported from Saudi Arabia [16], Algeria [17] and Mozambique 71.7% [18]. On the other hand, the prevalence of HPV 16 and HPV 18 in the previous study from Syria was 88.6% (39/44) and the prevalence of all the 7 types detected in that study was 95.45% [10]. In addition, reports from different geographical regions showed different prevalence rates for HPV 16 and 18 such as in Malaysia [19], Sudan [20] and Uganda [21].…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Similar detection rates of these two HPV types have been reported from Saudi Arabia [16], Algeria [17] and Mozambique 71.7% [18]. On the other hand, the prevalence of HPV 16 and HPV 18 in the previous study from Syria was 88.6% (39/44) and the prevalence of all the 7 types detected in that study was 95.45% [10]. In addition, reports from different geographical regions showed different prevalence rates for HPV 16 and 18 such as in Malaysia [19], Sudan [20] and Uganda [21].…”
Section: Resultssupporting
confidence: 60%
“…These incidence rates differ from the rates reported by Darnel et al [10] which were 47.7% and 40.9% for HPV 16 and HPV 18 respectively. However, the distribution of these two HPV types in our study is quite similar to a report from Iran which showed HPV 16 and HPV18 prevalence of 60% and 22.2% respectively [23].…”
Section: Resultscontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, ID1 regulates the effects of transcription factors on target genes. Infection by high-risk human papilloma viruses (HPVs) is considered to be the central cause of invasive cervical cancer, suggesting that high-risk HPVs can enhance the progression of human cervical cancer through ID1 regulation (Darnel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%